Case Study : The Application of Extracorporeal Shockwave Therapy (ESWT), Transverse Friction Massage and Hold Relax Exercise On Movement and Function of Ankle Joint Due to Calcaneus Spur Dextra - Friska Adelia; Juliastuti; Imam Haryoko; Yudiansyah (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background : Calcaneal spurs are a common cause of heel pain. Calcaneus Spur is an abnormal bony protrusion condition. It can occur anywhere along the calcaneal tuberosity. It is caused by pressure in the region of the plantar aponeurosis attachment to the calcaneal bone. This causes heel pain, the pain will be more severe when waking up in the morning. Objective: This case study was aimed to determine the effect of Extracorporeal Shockwave Therapy (ESWT), transverse friction massage and hold relax exercise on movement and function ankle joint disorders caused by calcaneus spur dextra. Methods: This case studies were carried out 6 times for 2 weeks on one patient, female 44 years old with calcaneus spur dextra condition by evaluating the degree of pain by using the Visual Analogue Scale (VAS), Joint Range of Motion (RoM) by using a goniometer and functional activity ability of the foot by using Foot Function Index (FFI) questionnaire. Results: There was a decrease of unmotion pain degree from VAS 2 to VAS 0, motion pain degree from VAS 3 to VAS 2, while tenderness pain degree decreased from VAS 7 to VAS 4. There was an increase on movement of plantar flexi ankle joint dextra from (S) 300-00-200 to (S) 400-00-200, and the FFI value decreased from 95% to 61% at the end of therapy. Conclusion: The application of intervention Extracorporeal Shockwave Therapy (ESWT), transverse friction massage and hold relax exercise can significantly reduce the motion pain on movement of plantar flexi dextra, tenderness pain around calcaneus, increase the RoM plantar flexi ankle joint dextra, and functional activity ability of the foot as well on calcaneus spur dextra condition.